2016
DOI: 10.1016/j.biomaterials.2016.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Systematic optimization of an engineered hydrogel allows for selective control of human neural stem cell survival and differentiation after transplantation in the stroke brain

Abstract: Stem cell therapies have shown promise in promoting recovery in stroke but have been limited by poor cell survival and differentiation. We have developed a hyaluronic acid (HA)-based self-polymerizing hydrogel that serves as a platform for adhesion of structural motifs and a depot release for growth factors to promote transplant stem cell survival and differentiation. We took an iterative approach in optimizing the complex combination of mechanical, biochemical and biological properties of an HA cell scaffold.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
195
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 54 publications
1
195
0
Order By: Relevance
“…Stem cells in these diferent biomaterials had a diverse behaviour related with mechanical properties of the scafold and conirm that stifness is an important factor [37].…”
Section: Tissue Engineering and Scafold Mechanical Propertiesmentioning
confidence: 63%
See 1 more Smart Citation
“…Stem cells in these diferent biomaterials had a diverse behaviour related with mechanical properties of the scafold and conirm that stifness is an important factor [37].…”
Section: Tissue Engineering and Scafold Mechanical Propertiesmentioning
confidence: 63%
“…For example, Moshayedi et al [37] developed a hydrogel material to control neural cells fate in vivo. In this study, an injectable hydrogel was designed and showed to promote survival and diferentiation towards immature states of human neural progenitor cells.…”
Section: Tissue Engineering and Scafold Mechanical Propertiesmentioning
confidence: 99%
“…Many factors can control cell fate, yet few have been tested in combination with cell delivery in a hydrogel delivery system for stroke. Moshayedi et al (2016) encapsulated hiPSC-derived NPCs in HA gels modified with MMP-cleavable sequences for degradation in the brain, as well as soluble factors, BDNF and BMP4, and adhesive laminin peptides, YIGSR and IKVAV (Moshayedi et al, 2016). The authors found that after injection of the hydrogel with cells into the stroke-injured mouse brain, BDNF and BMP4 promoted astrocytic differentiation whereas the laminin sequences promoted neuronal differentiation.…”
Section: Differentiation Of Transplanted Cellsmentioning
confidence: 98%
“…The differentiation of cells cultured on fibrous scaffolds can be controlled by tuning the thickness of the fibers; rat NSCs cultured on polyethersulfone fiber meshes differentiate preferentially into oligodendrocytes on smaller diameter fibers and into neurons on wider diameter fibers (Christopherson et al, 2009). Others have seen an increase in NSC differentiation in vivo with the use of HA hydrogels (Lam et al, 2014;Führmann et al, 2016;Moshayedi et al, 2016).…”
Section: Promoting Cell Differentiation and Integrationmentioning
confidence: 99%
See 1 more Smart Citation